Hadith #995 - Sahih Muslim - Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة (Sahih Muslim)
I met Thauban, the freed slave. of Allah’s Messenger (ﷺ), and asked him to tell me about an act for which, if I do it, Allah will admit me to Paradise, or I asked about the act which was loved most by Allah. He gave no reply. I again asked and he gave no reply. I asked him for the third time, and he said: I asked Allah’s Messenger (ﷺ) about that and he said: Make frequent prostrations before Allah, for you will not make one prostration without raising you a degree because of it, and remo
Grade: Sahih

Hadith #1158 - Sahih Muslim - Ma'dan bin Abi Talha معدان بن أبي طلحة ويقال بن طلحة (Sahih Muslim)
‘Umar b. Khattab, delivered the Friday sermon and he made a mention of the Messenger of Allah (ﷺ) and Abu Bakr. He (further) said: I saw in a dream that a cock pecked me twice, and I perceive that my death is near. Some people have suggested me to appoint my successor. And Allah would not destroy His religion. His caliphate and that with which He sent His Apostle (ﷺ) If death approaches me soon, the (issue) of Caliphate (would be decided) by the consent of these six men with whom the Messe
Grade: Sahih